The influence of urban environment factors on the growth of horse chestnut Aesculus Hippocastanum L. - Szymon Józef Łukasiewicz (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: In the years 1995–1999, at 21 sites within the broadly understood center of Poznań, research on the development of chestnut Aesculus hippocastanum L. was carried out. As part of this research, selected environmental factors were analysed. The aim was to become familiar with the conditions of tree development in the urban and industrial agglomeration of Poznań.